Virtual reality - Ferreira, Kauane L Costa; Barbosa, Andrea Teresa Riccio (Seven Editora, 2023)
Research Objective: To develop a Virtual Reality (VR) application for the practice of human anatomy. Context: The search for innovation in education is a global problem, the need for new ways to achieve it has created concern around the world. Problem: Develop appropriate technologies as a way of supporting practical teaching with the impossibility of face-to-face practical classes. Proposed solution: Develop a work with the aim of creating, at low cost, a virtual laboratory of human anatomy, which allows the simulation of practical classes. Method: empirical research, to define characteristics for the development of a virtual anatomy laboratory in the health area; descriptive to delimit the pertinent content in a virtual laboratory of human anatomy of the locomotor system. The data were used for the development of the laboratory where Blender 3D and JavaScript software were used, both free licenses. Summary of results: economic and infrastructure in public universities, from the implementation of a VR laboratory for teaching anatomy. Contributions: As a scientific contribution, the developed application will make the information accessible to a greater number of users, facilitating practical work. The financial contribution will lead to a reduction in expenses with the purchase of corpses for practice laboratories and with a reduction of physical facilities in public educational institutions. Impact in the IS area: In the educational area, where the student of the health area will know advantages and potentialities that the use of VR in teaching can offer in the practical learning process.DOI:https://doi.org/10.56238/alookdevelopv1-187